2016
DOI: 10.1021/acs.jnatprod.6b00131
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopeptide Alkaloids from Hymenocardia acida

Abstract: Four cyclopeptide alkaloids (1-4) were isolated from the root bark of Hymenocardia acida by means of semipreparative HPLC with DAD and ESIMS detection and conventional separation methods. Structure elucidation was performed by spectroscopic means. In addition to the known compound hymenocardine (1), three other alkaloids were isolated for the first time from a natural source. These included a hymenocardine derivative with a hydroxy group instead of a carbonyl group that was named hymenocardinol (2), as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…The in vitro antiplasmodial activity against P. falciparum strain K1 and the cytotoxicity against MRC-5 cells was determined for ten cyclopeptide alkaloids, isolated from the stem bark of Ziziphus nummularia , Ziziphus spina-christi , Ziziphus jujuba , and the root of Hovenia dulcis , all belonging to the Rhamnaceae family, and the results are shown in Table 1 . The results that were previously reported for cyclopeptide alkaloids isolated from the root bark of H. acida (Phyllanthaceae) and the roots of Z. oxyphylla (Rhamnaceae) [ 6 , 7 ] are also included in this table. The highest antiplasmodial activity was found for spinanine-B ( 3 ), with an IC 50 value of 2.1 μM and without cytotoxic effects in concentrations of 64.0 μM or less.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The in vitro antiplasmodial activity against P. falciparum strain K1 and the cytotoxicity against MRC-5 cells was determined for ten cyclopeptide alkaloids, isolated from the stem bark of Ziziphus nummularia , Ziziphus spina-christi , Ziziphus jujuba , and the root of Hovenia dulcis , all belonging to the Rhamnaceae family, and the results are shown in Table 1 . The results that were previously reported for cyclopeptide alkaloids isolated from the root bark of H. acida (Phyllanthaceae) and the roots of Z. oxyphylla (Rhamnaceae) [ 6 , 7 ] are also included in this table. The highest antiplasmodial activity was found for spinanine-B ( 3 ), with an IC 50 value of 2.1 μM and without cytotoxic effects in concentrations of 64.0 μM or less.…”
Section: Resultsmentioning
confidence: 98%
“…Nummularine-B was found to be moderately active (IC 50 value of 10.3 μM) against Plasmodium falciparum , but not mauritine-L and nummularine-B methiodide [ 5 ]. Our research group has previously reported the antiplasmodial activity of cyclopeptide alkaloids from Hymenocardia acida and Ziziphus oxyphylla [ 6 , 7 ]. Based on these results, some preliminary conclusions concerning their SAR (structure-activity relationship) were drawn, but given the fact that the number of compounds tested in each of these studies was relatively small, it was not possible to draw definite conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 45 together with others shows high and specific activities against P. falciparum [39] Evidence-Based Complementary and Alternative Medicine A new alkaloid, tavoyanine A (56), and other known alkaloids, roemerine (57), laurolitsine (58), boldine (59), and sebiferine (60) Aporphine alkaloids (56)(57)(58)(59) and morphinandienone (60) Leaf 1.10. Quinoline Alkaloids.…”
Section: Ancistrocladus Ileboensismentioning
confidence: 99%
“…None of the compounds were toxic to the non-cancerous Vero cells, except for 6, which showed weak action with an IC 50 of 48.2 mM. To date, only two studies on the in vitro cytotoxicity of natural rhamnaceous cyclopeptide alkaloids have been reported, 38,49 although the weak activity of some representative synthetic 13-and 15-membered ring cyclopeptides was described recently. 50…”
Section: Resultsmentioning
confidence: 99%